PENGARUH EKSTRAK DAUN SALAM (Syzygium polyanthum (Wight.) Walp.) TERHADAP TINGKAT HIDROLISIS PATI, AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORI NASI INSTAN [The Effect of Extract Bay Leaf (Syzygium polyanthum (Wight.) Walp.) on the Level of Starch Hydrolysis, Antioxidant Activity and Sensory Properties of Instant Rice] - Rahmadi, Isnaini; Nurdin, Samsu Udayana; Astuti, Sussi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
In some Asian countries, diabetes mellitus (DM) is suggested to be close related to their rice daily intake as rice intake contributes significantly into their blood glucose level. Threrefore, for patient of DM or people who has high risk of digestibility of starch should be lowered. This research was aimed to obtain an optimal concentration of bay leaf extract that produces instant rice with low levels of starch hydrolysis, the high antioxidant activity and sensory properties are preferred. The experiment was arranged in a Complete Randomized Block Design (CRBD) with six bay leaf extract concentrations which were 0%, 5%, 10%, 15%, 20% and 25% of the solution volume for cooking. The results showed the addition of the bay leaf extract did not affect the rate of starch hydrolysis and total phenol of instant rice, but it effected on antioxidant activity and sensory properties of instant rice. The best treatment of the instant rice with the addition of bay leaf extract at 0 % who has the degree of hydrolysis of starch by 15.21 %, the antioxidant activity by 79.44 %, total of phenol about 0.19 ppm GAE, the percentage of panelists with like criteria to odor about 49.52 %, the taste 59.05 %, color 86.67 % and fluffier 41.90%.Keywords: antioxidants, bay leaves, hydrolysis of starch, instant rice